(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
The research examined School-Based Management Committee and delivery of the trade subjects in Alimosho Education Zone of Lagos State. Two research questions and two hypotheses were answered and tested, respectively. The study adopted a descriptive survey design. Multi-stage sampling procedure was adopted for the study. Simple random sampling technique was adopted to select 13 public senior secondary schools in Alimosho Education Zone. Afterwards, purposive sampling technique was used to select 13 principals, 26 counsellors, 13 PTA secretaries and 52 trade subject teachers. Thus, a sample size of 104 respondents was used for the study. A researcher-constructed questionnaire was used for the study with reliability coefficient of 0.75. Data obtained were analysed using Analysis of Variance (ANOVA) at 0.05 level of significance. The results showed that there was no significant difference in the opinions of respondents on School-Based Management Committees in financial management and monitoring and evaluation in relation to the delivery of the trade subjects. Based on the findings, the study recommended thatoperationalization of financial management should be more opened in order to accommodate the participation of the SBMC in the provision of funds, ensuring accountability and the judicious use of available fund, and;External supervisory bodies and school administrators should synergise with the SBMC in ensuring a more effective monitoring and evaluation process of the delivery of the trade subjects.